2015
DOI: 10.1007/s00436-015-4455-6
|View full text |Cite
|
Sign up to set email alerts
|

Two different myiasis cases in southeast of Turkey: ophthalmomyiasis and cutaneous myiasis

Abstract: Myiasis has become increasingly prevalent, particularly when human activity is carried out in environments with poor hygiene. We reported two cases of human myiasis in this paper. All of myiasis cases initially presenting to the Emergency Department of Kilis State Hospital in Turkey were identified. We present one case of ophthalmomyiasis caused by Oestrus ovis and one case of cutaneous myiasis caused by Lucilia sericata. Both of the myiasis cases were reported from rural area case limiting the exposure to adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Similarly, Dokur et al (2015) reported two cases of myiasis in rural areas of southeast Turkey. Abundant household animals and unhealthy environment also participate in the emergence of new cases of myiasis (Batista-da-Silva et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Dokur et al (2015) reported two cases of myiasis in rural areas of southeast Turkey. Abundant household animals and unhealthy environment also participate in the emergence of new cases of myiasis (Batista-da-Silva et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The larvae are photophobic in nature and tend to conceal themselves in the upper and lower fornix (Zumpt 1965). Other cases of ophthalmomyiasis externa caused by O. ovis had been reported from France by Nitzulescu et al (1966), from Turkey (Dokur et al 2015) and from Saudi Arabia (Al-Amry et al 2014) and three cases of conjunctival myiasis from Italy (Zammarchi et al 2014). Besides O. ovis, many studies have reported the occurrence of ophthalmomyiasis externa caused by the human botfly, Dermatobia hominis (Goodman et al 2000;Denion et al 2004;Wakamatsu and Pierre-Filho 2006;Price et al 2007;Alsaif et al 2014).…”
Section: Ophthalmomyiasis Externamentioning
confidence: 91%
“…A pus-filled ulcerative wound under the flange of the tube was found infested with maggots of C. bezziana. A case of cutaneous myiasis caused by Lucilia sericata had been reported from Turkey (Dokur et al 2015).…”
Section: Traumatic Myiasismentioning
confidence: 99%
“…Myiasis can also be categorized as gastrointestinal, urogenital, ocular, nasopharyngeal, auricular, and cutaneous depending on the site of larval invasion (447). In Turkey, several cases of myiasis in humans were reported from different regions (448)(449)(450).…”
Section: Diptera (True Flies)mentioning
confidence: 99%